1978
DOI: 10.1007/bf01477062
|View full text |Cite
|
Sign up to set email alerts
|

�ber die ACTH-Kortikoid-Relation bei essentieller Hypertonie in Abh�ngigkeit von der Plasma-Renin-Aktivit�t (PRA)

Abstract: Patients with essential hypertension were studied for the reaction of the hypophyseal-adrenal-system before and during insulin hypoglycemia test. We found in our results that the mean total corticoid levels in plasma of hypertensive patients with low or high PRA are significantly higher than control levels. In insulin hypoglycemia test the mean corticoid levels of patients with normal and high PRA do not differ from the mean levels found in normal individuals whereas hypertensive patients with low PRA have sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
1982
1982

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Henry (22) postulated that increased ACTH release is one of the effects of psychosocial stress and has demonstrated that this kind of stress can be associated with hypertension accompanied by high glucocorticoid and mineralocorticoid levels in rats. Higher ACTH levels in subjects with essential hypertension than in normotensives have been reported (24). It has…”
Section: Discussionmentioning
confidence: 92%
“…Henry (22) postulated that increased ACTH release is one of the effects of psychosocial stress and has demonstrated that this kind of stress can be associated with hypertension accompanied by high glucocorticoid and mineralocorticoid levels in rats. Higher ACTH levels in subjects with essential hypertension than in normotensives have been reported (24). It has…”
Section: Discussionmentioning
confidence: 92%